How does infliximab work in rheumatoid arthritis? - Maini, R; Feldmann, M (2002)
Since the initial characterization of tumor necrosis factor alpha (TNFalpha), it has become clear that TNFalpha has diverse biologic activity. The realization that TNFalpha plays a role in rheumatoid arthritis (RA) has led to the development of anti-TNF agents for the treatment of RA. Infliximab, a chimeric monoclonal antibody that specifically, and with high affinity, binds to TNFalpha and neutralizes the cytokine, is currently approved for the treatment of RA and Crohn's disease, another immune-inflammatory disorder. In addition to establishing the safety and efficacy of infliximab, clinical research has also provided insights into the complex cellular and cytokine-dependent pathways involved in the pathophysiology of RA, including evidence that supports TNFalpha involvement in cytokine regulation, cell recruitment, angiogenesis, and tissue destruction.